2010
DOI: 10.3944/aott.2010.2293
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and functional outcomes and proprioception after a modified accelerated rehabilitation program following anterior cruciate ligament reconstruction with patellar tendon autograft

Abstract: We had satisfactory clinical, proprioceptive, and functional results in achieving dynamic and static stability of the knee with the modified accelerated rehabilitation program after ACL reconstruction with a PT graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
9

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 37 publications
1
35
0
9
Order By: Relevance
“…29 Although several studies have reported persistent symmetry deficits in hop tests following ACLR, 4,13,16 only recently have researchers performed thorough analyses of the biomechanics associated with the observed functional deficits during these maneuvers. 18,21,31 As yet, to the authors' knowledge, no study has comprehensively investigated lower extremity kinematics, muscular strength, and functional performance in a homogeneous group of patients 6 to 9 months post-ACLR. Nor has there been a study that has evaluated both the propulsion and landing phases by investigating the kinematics of the hip, knee, and ankle during these commonly used hop tests.…”
Section: U U Resultsmentioning
confidence: 99%
“…29 Although several studies have reported persistent symmetry deficits in hop tests following ACLR, 4,13,16 only recently have researchers performed thorough analyses of the biomechanics associated with the observed functional deficits during these maneuvers. 18,21,31 As yet, to the authors' knowledge, no study has comprehensively investigated lower extremity kinematics, muscular strength, and functional performance in a homogeneous group of patients 6 to 9 months post-ACLR. Nor has there been a study that has evaluated both the propulsion and landing phases by investigating the kinematics of the hip, knee, and ankle during these commonly used hop tests.…”
Section: U U Resultsmentioning
confidence: 99%
“…Proprioception at knee joint is often measured with the "passive and AJPS" method. [19][20][21][22] AJPS stimulates both the joint and the muscle receptors and helps measure the afferent paths in a more functional manner. 11 However, these two methods are conducted without applying weight on the knee joint.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are studies in the literature that were performed with different grafts and that compared proprioception at 15°and 60°flexion following the ACL reconstruction with the healthy control group. [19][20][21][22][27][28][29] Risberg et al found the knee proprioception similar at 15°knee flexion angle in the patient and the control group approximately 2 years after the anterior cruciate ligament reconstruction with patellar tendon autograft. 27 Another study used AJPS evaluated proprioception on 15 patient and 15 healthy elite sportsmen with the isokinetic dynamometer 19 months after the ACL reconstruction with hamstring tendon autograft.…”
Section: Discussionmentioning
confidence: 99%
“…The static and dynamic postural stability was similar between the involved and uninvolved side knees in each group. An injury to the ACL can compromise the neuromuscular function of the knee joint, resulting in impaired proprioception and dynamic stability of the knee joint [21][22][23]. Recent studies have suggested that the menisci also have important roles in neuromuscular control of the knee joint [1,24,25].…”
Section: Discussionmentioning
confidence: 99%